A COLLABORATIVE SPATIAL DATABASE FOR THE INVENTORY OF TREES IN THE UNIVERSITY OF THE PHILIPPINES DILIMAN CAMPUS - Aranas, R.K.D.; Abuel, M.C.; del Rosario, E.; Locsin, J.D.C.; Villanueva, M.J. (Philippine Engineering Journal, 2013)
Urban trees are defined as individuals, groups, and stands of trees and remnant forests with amenity values found in urban areas or areas with human structures on site. These resources provide a wide variety of ecologic and economic uses. These assets need to be accounted for and protected, hence the need to monitor their status by inventory. Urban trees management would be greatly enhanced by setting up a spatial database system. Activities to be undertaken include spatial database design, data acquisition, database build-up, web GIS set-up and installation, and developing methods for collaboration. Through the use of modern technology i.e. mobile and web technology, we were able to come up with an initial database for tree inventory of UP Diliman. The utilization of open source platform facilitates easier and cheaper option for updating of the components of our prototype. Latest developments in mobile technology i.e. GPS technology, Android OS and Smart Measure app in the market enables us to propose a viable option for updating our tree database. Data integration from different field observations is facilitated through an initial spatial database model as proposed in this research. Key Words: urban tree inventory, web GIS, collaborative spatial database, mobile technology application